Liberal Attachments: Cultivating Civic Identifications. Issue 6 (21st June 2021) - Gottlieb, Derek; Shuffelton, Amy B.
Abstract : In the immediate aftermath of the November 2016 election, Mark Lilla argued in the New York Times that in order to win, the Democratic party would need to replace identity politics with a unifying vision of citizenship. In this essay, Derek Gottlieb and Amy Shuffelton explore Lilla's use of the two major terms — identity and citizenship — revealing them to be equally susceptible to expansion, extension, and antipolitical corruption. Using the work of Richard Rorty, Stanley Cavell, Iris Marion Young, and Rita Felski, Gottlieb and Shuffelton amend the dichotomy that Lilla draws, showing that the project of fostering a national imaginary capable of unifying publics across differences will require a process of what Felski calls "identification." The authors conclude by noting and describing civics courses as the ideal settings for the cultivation of a willingness and ability to identify across differences.